KAJIAN EKSPERIMENTAL PENGARUH PENGGUNAAN ELECTRONIC CONTROL UNIT AFTERMARKET PADA DAYA, TORSI, EMISI DAN KONSUMSI BAHAN BAKAR SEPEDA MOTOR 150CC - Arka Dwinanda Soewono; Marten Darmawan; Josep Halim (Jurnal Rekayasa Mesin, 2023)
To improve motorbike performance, simple modifications are often applied using an aftermarket Electronic Control Unit (ECU). However, scientific studies on this particular topic are still limited. Therefore, the purpose of this research is to examine the effect of the aftermarket Juken 5 ECU on the power, torque, emissions, and fuel consumption of the Yamaha R15-V3 bike. The results of the dynamometer testing showed that the motorcycle with the Juken 5 ECU experienced an average increase of 8.09 ± 1.30% in power and 7.79 ± 1.31% in torque, respectively, at 5500 – 11000 rpm. However, the concentrations of Carbon Monoxide and Hydrocarbon emissions also increased by 170% and 360%, respectively. Particulate emission measurements also revealed that the Juken 5 ECU usage resulted in a significant increase in particulate counts. Compared to the standard ECU, motorcycles equipped with the Juken 5 ECU produced 89% and 145% more particulates in the size range of 0.3 – 0.374 μm and 0.374 – 2.685 μm, respectively. The performance and emission data analysis results indicated that the increase in power and torque achieved by the Juken 5 ECU is simply due to more fuel being injected into the combustion chamber.  This finding was supported by the results of fuel consumption testing, where using the aftermarket ECU increased motorcycle fuel consumption by 63.6%.